Exploring the Chemistry of Alkaloids from Malaysian Mitragyna speciosa (Kratom) and the Role of Oxindoles on Human Opioid Receptors - Nelson Jeng‐Yeou Chear; Francisco León; Abhisheak Sharma; Raju S. Kanumuri; Grant Zwolinski; Khalil A. Abboud; Darshan Singh; Luis F. Restrepo; Avi Patel; Takato Hiranita; Surash Ramanathan; Aidan J. Hampson; et al. (2021)
Ten indole and oxindole alkaloids (1–10) were isolated from the freshly collected leaves of Malaysian Mitragyna speciosa (Kratom). The chemical structures of these compounds were established on the basis of extensive 1D and 2D NMR and HRMS data analysis. The spectroscopic data of mitragynine oxindole B (4) are reported herein for the first time. The spatial configuration of mitragynine oxindole B (4) was confirmed by single-crystal X-ray diffraction. Simultaneous quantification of the isolated alkaloids in the M. speciosa leaf specimens collected from different locations in the northern region of Peninsular Malaysia was also performed using UPLC-MS/MS. The oxindole alkaloids (1–4) and the indole alkaloid (10) were assessed for binding affinity at opioid receptors. Corynoxine (1) showed high binding affinity to μ-opioid receptors with a Ki value of 16.4 nM. Further, corynoxine (1) was 1.8-fold more potent than morphine in rats subjected to a nociceptive hot plate assay. These findings have important implications for evaluating the combined effects of the minor oxindole alkaloids in the overall therapeutic activity of M. speciosa.